May Platelet Indexes Be Effective in Intracranial Hemorrhage of Preterm Infants? - Hakyemez Toptan, Handan; Karadağ, Nilgün; Karatekin, Güner (Cerrahpaşa Medical Journal, 2023)
Objective: Preterm newborns are at increased risk of developing morbidities including germinal matrix hemorrhage and intraventricular hemorrhage. In this study, we aimed to examine the efficacy of platelet parameters on germinal matrix hemorrhage and intraventricular hemorrhage in preterm newborns. Methods: A total of 54 preterm infants between 23 and 36 gestational weeks, and followed-up with germinal matrix hemorrhage and intraventricular hemorrhage in our neonatal intensive care unit were included in our study. Patients’ demographic data such as age and gender, birth weight, intrauterine growth retardation, blood transfusion, platelet transfusion, duration of hospitalization, and outcomes were recorded. The infants were divided into 2 groups according to Volpe’s germinal matrix hemorrhage and intraventricular hemorrhage classification as mild stage germinal matrix hemorrhage and intraventricular hemorrhage (group 1) and severe stage germinal matrix hemorrhage and intraventricular hemorrhage (group 2). Results: The mean birth weight of all infants was 1005.74 ± 432.01 g in all infants. The mean gestational week was found as 27.15 ± 2.99 in all infants. Platelet transfusion was performed in 8 (25%) patients in group 1 and 17 (77.27%) patients in group 2, and the difference was statistically significant (P < .001). The mean platelet count was found as 187 798.15 ± 77 259.93, the mean platelet volume as 7.55 ± 1.12, and the mean platelet mass index as 1489.44 ± 591.06 in all infants. There was no significant difference between the groups in terms of mean platelet volume, platelet count, and platelet mass index. There was no statistically significant correlation between the platelet indices and any grade germinal matrix hemorrhage and intraventricular hemorrhage. Conclusion: No statistically significant difference was found between the patients with mild stage germinal matrix hemorrhage and intraventricular hemorrhage and severe stage germinal matrix hemorrhage and intraventricular hemorrhage in terms of platelet count, mean platelet volume, and platelet mass index. In addition, no significant correlation was observed between these indices and any grade germinal matrix hemorrhage and intraventricular hemorrhage. Cite this article as: Hakyemez Toptan H, Karadağ N, Karatekin G. May platelet indexes be effective in intracranial hemorrhage of preterm infants? Cerrahpaşa Med J. 2023;47(1):64-67.